TEACHERS’ PERFORMANCE IN INSTILLING DISCIPLINARY CHARACTERFOR GRADE IV STUDENTS - Felensky Nurberlian; M. Hosnan; Rina Yuliana (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to describe the planning process for embedding the disciplinary character in students and to describe the process of embedding disciplinary character in students as well as the results of embedding the disciplinary character at SDN Banjarsari 5 Serang. The method of this research was descriptive qualitative which was through data reduction, data presentation, and drawing conclusions or verification. This research was conducted by triangulating data such as interviews and observations. The result of interviews found that the teacher implemented the process of embedding the disciplinary characters in students during the learning process at grade IV. Then, based on observations regarding theprocess of embedding student discipline character, it was concluded that the teacherimplemented the disciplinary character in students while the results of the interviews withteachers and the student observations concluded that students had a good impact by achievingthe goal of knowing the teacher's performance in instilling students’ discipline character.